Etika Notaris di Media Sosial Ketika Profesionalisme Dipertaruhkan - Verginia Nadea, Lydia; Ridwan, Fully Handayani Ridwan (Universitas Medan Area, 2025)
Notary professional ethics in the use of social media, which is increasingly relevant in the digital era. As a profession that prioritizes integrity and confidentiality, notaries are faced with new challenges related to the misuse of social media that can damage their reputation and professionalism. This study aims to analyze the impact of ethical violations committed by notaries on social media, both on personal reputation, legal sanctions, and public trust in the notary profession as a whole. The methods used in this study are literature studies and case analysis. The results of the study indicate that ethical violations on social media can reduce the credibility of notaries, cause loss of clients, and damage the image of the profession. This study also found that although there are regulations that govern it, the implementation of professional ethics in the digital realm still requires more attention from the Honorary Council of the Indonesian Notary Association (INI) to maintain the professionalism and integrity of the notary profession